Science Communication: The Case of Maratona da Saúde TV program - Souza, Mariana Adeodato Alves de; Oliveira, Andrea (Revista Española de Comunicación en Salud, 2019)
Introduction: Scientific communication and a great approximation of science with society are strategies for raising funds for scientific research. Objective: The goal of the study is to examine the narratives used in the television program of Maratona da Saúde as a communicative tool for the effectiveness of fundraising. Methodology: a content analysis of the Television Program of the five editions of Maratona da Saúde was carried out, based on the work of Luís Mauro Sá Martino (2016). Results: the results obtained indicate that the Maratona da Saúde is, in fact, an innovative Project, whose success lies in the mixture of various forms of health and science narratives, using accessible language, managing to gradually involve the viewer, which contributes to make him a potential donor. Conclusion: the studied TV show contributes to the education and learning of Portuguese society about science, health and the importance of its promotion.
Keywords: science communication; entertainment; fundraising; narrative; Maratona da Saúde; Portugal